Adaptabilidade na produção de massa verde e grãos de genótipos de milho no Tocantins - Carvalho, Edmar Vinícius De; Afférri, Flávio Sérgio; Pelúzio, Joênes Muci; Santos, Weder Ferreira Dos; Bicudo, Silvio José [UNESP] (Universidade Federal do Ceará, 2014)
Different growth conditions give genotypes a different response to each situation. To reduce the effect of this interaction, analyses of stability and adaptability are undertaken, which assist in choosing the genotypes. However, often a genotype can have a variety of purposes, causing problems to farmers in some situations, and the use of specific genotypes could be a solution. The objective of this research was to study the adaptability and stability of maize genotypes in the South Central region of the state of Tocantins, Brazil, and to classify them according to trends in productivity goals: grain or green weight. Eight experiments were conducted in two towns in Tocantins in the 2010 off-season and the 2010/2011 season, in which 16 maize genotypes were evaluated. The total plant green weight and grain production (g plant-1) were evaluated and then used in the analysis of stability and adaptability. Later it was sought to classify the trends in productivity goals for the genotypes. The genotypes P09, P12, P10, H02 and H01 displayed a superior classification of the regression coefficient for grain production compared to total plant green weight, with the opposite happening in the P02 and P01 genotypes. Genotype H01, as regards grain production, was adapted for favourable environments and displayed a tendency for this characteristic as a productive goal. Unlike the P08 and P02 genotypes that were adapted for both environments or for favourable environments respectively, as regards total plant green weight, and show a trend in productive goals for this characteristic.

Condições distintas de cultivo fazem com que a resposta dos genótipos seja diferente em cada situação. Para amenizar o efeito desta interação são realizadas análises de adaptabilidade e estabilidade, que auxiliam na escolha dos genótipos. Porém, muitas vezes, um genótipo apresenta diversas finalidades, causando problemas ao agricultor em algumas situações e, o uso de genótipos específicos, poderia ser uma solução. O objetivo desta pesquisa foi estudar a adaptabilidade e estabilidade de genótipos de milho na região Centro-Sul do Estado do Tocantins, e classificá-los, quanto a tendência da finalidade produtiva: grãos ou massa verde. Foram realizados oito experimentos em dois municípios do Tocantins na entressafra 2010 e na safra 2010/2011, sendo avaliados 16 genótipos de milho. Avaliou-se a massa verde total da planta e a produção de grãos (em g planta-1), as quais foram usadas na análise de adaptabilidade e estabilidade e, posteriormente buscou-se classificar a tendência da finalidade produtiva dos genótipos. Os genótipos P09, P12, P10, H02 e H01 apresentaram classificação do coeficiente de regressão superior na produção de grãos em relação à massa verde total da planta, acontecendo o contrário com os genótipos P02 e P01. O genótipo H01, quanto à produção de grãos, foi adaptado a ambientes favoráveis e apresentou tendência da finalidade produtiva para esta característica. Ao contrário dos genótipos P08 e P02, que foram adaptados a ambos ambientes e a ambientes favoráveis, respectivamente, quanto à massa verde total da planta e, obtiveram tendência da finalidade produtiva para esta característica.
Adaptability in fresh weight and grain production in maize genotypes in Tocantins, Brazil
Keywords: Milho-melhoramento genético; Interação genótipo-ambiente; Adubação orgânica; Maize-breeding; Genotype-environment interaction; Organic Fertilisation